Análisis comparado de los factores institucionales que impiden la reelección de los gobernadores argentinos. (2014)
The purpose of this article is to explain why most of the Argentine governors who reformed provincial constitutions providing the possibility of reelection were later able to reach their objective while others did not. To do so, I will proceed to identify which are the institutional factors that prevent the reelection of these reformist governors, using a qualitative comparative methodology (QCA).